Persistence and Extent of Neonatal Brachial Plexus Palsy: Association with Number of Maneuvers and Duration of Shoulder Dystocia - Morgen S. Doty; Suneet P. Chauhan; Kate W.-C. Chang; Leen Al-Hafez; Connie McGovern; Lynda J.-S. Yang; Sean C. Blackwell (Thieme Medical Publishers, Inc., 2020)
Objective The main objective of this article is to determine if persistence of neonatal brachial plexus palsy (NBPP) following shoulder dystocia was associated with maneuvers used or duration of impacted shoulder. Study Design Retrospective review of children with NBPP and documented shoulder dystocia. Student t-tests and chi-squared tests were used to compare outcomes when shoulder dystocia resolved with > 3 versus ≤ 3 maneuvers or duration > versus ≤ 120 seconds. Relative risk (RR) with 95% confidence intervals (CI) was calculated. Results Among 46 children with NBPP and shoulder dystocia, incidence of persistence was significantly higher at 2 years of age when > 3 versus ≤ 3 maneuvers were used (100 vs. 62%; RR: 1.6, 95% CI: 1.2-2.2). When resolution of impacted shoulder lasted >120 versus ≤ 120 seconds, NBPP at 2 years was significantly more likely (100 vs. 63%; RR: 1.6, 95% CI: 1.1-2.2). Injury to all five nerves of the brachial plexus was more likely if standard deviation lasted > 120 versus ≤ 120 seconds (RR: 2.2; 95% CI: 1.03-4.6). Conclusion Though the number of maneuvers used and duration of shoulder dystocia are associated with persistence of NBPP, the retrospective nature of the study of a selective cohort precludes recommendations changing the current management of shoulder dystocia.